Silver veins, dusty lungs : mining, water, and public health in Zacatecas, 1835-1946 - Gomez, Rocio (Professor of Latin American history) (Mexican experience., 2020)
"Rocio Gomez studies how the silver mining industry affected water resources and public health in the city of Zacatecas, Mexico, from 1835 to 1946"--